A Playwright for Practitioners: Reflections on Human Rights Storytelling and the Art of Naomi Wallace. (30th January 2017) - French, Nathaniel; Phillips, Brian
Abstract: As a feature of the Reviews Section of the Journal of Human Rights Practice, we include here the first in a new series on contemporary arts practitioners whose work we believe to be of particular relevance to activists, educators and scholars engaged with human rights practice. Nathaniel French, Literary Associate at New York City's Signature Theatre, and Brian Phillips, Reviews Editor of the Journal, begin this series with a set of reflections on the work of US playwright Naomi Wallace. Nathaniel French has been the dramaturg for two recent productions of Wallace's work at Signature Theatre. This two-part essay outlines how some of Wallace's plays might stimulate fresh thinking about those 'classic' personae of the human rights report and campaign: the victim, the witness, and the perpetrator.